Math, asked by anil5644g36, 9 months ago

please solve a notebook please please​

Attachments:

Answers

Answered by Anonymous
1

Answer:

don't have time

Answered by dna63
0

Step-by-step explanation:

We have,,

\sf{(5a-3b)(-a+6b)-(2a+3b)(3a-4b)}

\sf{=[-5a^{2}+30ab+3ab-18b^{2}]-[6a^{2}-8ab+9ab-12b^{2}]}

\sf{=-5a^{2}+30ab+3ab-18b^{2}-6a^{2}+8ab-9ab+12b^{2}}

\sf{=-5a^{2}-6a^{2}+33ab-ab-18b^{2}+12b^{2}}

\sf{=\boxed{\sf{-11a^{2}+32ab-6b^{2}}}}

___________________________________________

HOPE IT HELPS ❣️❣️❣️

Similar questions